Efek Model Penyimpanan Jagung (Zea mays L.) terhadap Kadar Gula Reduksi - Jefrianus Nino; Maria Magdalena Endah Mulat Satmalawati; Maria Afnita Lelang (Fakultas Pertanian, Universitas Timor, 2020)
Corn is a food material that is easily accepted by the community, because it is a staple food ingredient. One of the causes of decreased maize productivity is the ineffective maize storage model so that the need for seeds becomes less available and affects the quality of the maize. The habits of the people of TTU Regency generally save the corn harvest by fumigating it in the kitchen, storing it in barns, and storing corn drums. The three storage models are believed to be able to increase the shelf life of corn longer and avoid powder pests. However, in reality in the field resilience only covers the quantity (availability) aspect, while the quality aspect is not given much attention. In connection with the constraints experienced by the community, it is necessary to conduct a study to determine reducing sugar levels. The purpose of this study was to determine the storage model that can maintain quality and does not reduce reducing sugar levels in corn. This research was conducted from May to July 2014. The research method was carried out by testing in the laboratory. The tools used in the study were ovens, analytical scales, desiccators, and sample containers. The materials used were maize from the three storage models (fumigation, granary, and drum). The results showed that the highest reducing sugar content was in the drum storage model. In addition, the storage model for corn in the drum has the highest moisture content value of 15.26%.